2017
DOI: 10.2105/ajph.2017.303696
|View full text |Cite
|
Sign up to set email alerts
|

Injury Mortality in Individuals With Autism

Abstract: Individuals with autism appear to be at substantially heightened risk for death from injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 10 publications
1
73
0
4
Order By: Relevance
“…Although evidence of decreased life expectancy (Hirvikoski et al 2016; Guan and Li 2017) and poorer physical health in adulthood (Croen et al 2015) in ASD has only recently emerged, this evidence coupled with the rapidly increasing population of adults with ASD (Gerhardt and Lainer 2011) signals the need to better understand physical health, and factors that promote physical health, in ASD. It is likely that people with ASD who are otherwise disadvantaged have poorer physical health and access to health care throughout life, and this in combination with other factors, leads to worse physical health outcomes as individuals with ASD age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although evidence of decreased life expectancy (Hirvikoski et al 2016; Guan and Li 2017) and poorer physical health in adulthood (Croen et al 2015) in ASD has only recently emerged, this evidence coupled with the rapidly increasing population of adults with ASD (Gerhardt and Lainer 2011) signals the need to better understand physical health, and factors that promote physical health, in ASD. It is likely that people with ASD who are otherwise disadvantaged have poorer physical health and access to health care throughout life, and this in combination with other factors, leads to worse physical health outcomes as individuals with ASD age.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, a recent review found evidence for high rates of cardiovascular problems and mental health conditions (Cashin et al in press), and studies have additionally identified high rates of early parkinsonism (Starkstein et al 2015). Individuals with ASD also have a life expectancy that is between 20 and 36 years shorter than the general population (Hirvikoski et al 2016; Guan and Li 2017). Heightened adverse physical health outcomes in ASD may be partially explained by known health risk factors, including poor eating habits (Ho et al 1997), obesity (Ho et al 1997; Croen et al 2015), limited physical activity (Ho et al 1997), long-term psychotropic medication use (Esbensen et al 2009) and institutionalization (Krahn et al 2006).…”
mentioning
confidence: 99%
“…195 looks into the autistic life expectancy. While autism as a condition itself does not shorten life expectancy, the average life expectancy of a person with autism in the United States is 36, with suicide, infanticide, and medical neglect being some of the leading causes of death (Guan and Li 2017). Recent research from the Autism CRC of UNSW Sydney revealed that the mortality rates of those with ASD are more than twice those of the general population in New South Wales, Australia (Hwang et al 2019).…”
Section: )mentioning
confidence: 99%
“…Premature deaths among autistic individuals are largely attributable to injury (e.g., suffocation, asphyxiation, drowning, suicide), which may be impacted by factors such as substance use. 6 Moreover, chronic or frequent alcohol and substance use can worsen depression, anxiety, sleeplessness, and result in headaches and other stressors, 7-10 but research on substance use by autistic adolescents remains extremely limited. As a result, it is unknown how commonly these alcohol-related problems may be experienced by autistic adolescents and young adults.…”
Section: Introductionmentioning
confidence: 99%